2018
DOI: 10.1007/s12035-018-0976-1
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Excites Striatal Dopamine D1 and D2 Receptor-Expressing Neurons via Postsynaptic H1 and H2 Receptors

Abstract: The central histaminergic nervous system, originating from the tuberomammillary nucleus (TMN) of the hypothalamus, widely innervates almost the whole brain, including the basal ganglia. Intriguingly, the histaminergic system is altered in parkinsonian patients. Yet, little is known about the effect and mechanisms of histamine on different types of neurons in the basal ganglia circuitry. Here, by using anterograde tracing, immunostaining, patch clamp recording, and single-cell qPCR techniques, we investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 50 publications
3
31
1
Order By: Relevance
“…The increase in action potential frequency promoted by histamine in deep-layer cortical neurons is in accordance with the increased excitability previously reported for neurons in other regions of the CNS, namely thalamus (McCormick and Williamson, 1991), layer 6b of the primary somatosensory cortex (Wenger Combremont et al, 2016), entorhinal cortex (Cilz and Lei, 2017), ventral pallidum (Ji et al, 2018), striatum (Zhuang et al, 2018), and spinal cord (Wu et al, 2019). Furthermore, the lack of difference in H 1 R density supports that the electrophysiological changes observed in the offspring of diabetic rats rely mainly on morphological alterations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The increase in action potential frequency promoted by histamine in deep-layer cortical neurons is in accordance with the increased excitability previously reported for neurons in other regions of the CNS, namely thalamus (McCormick and Williamson, 1991), layer 6b of the primary somatosensory cortex (Wenger Combremont et al, 2016), entorhinal cortex (Cilz and Lei, 2017), ventral pallidum (Ji et al, 2018), striatum (Zhuang et al, 2018), and spinal cord (Wu et al, 2019). Furthermore, the lack of difference in H 1 R density supports that the electrophysiological changes observed in the offspring of diabetic rats rely mainly on morphological alterations.…”
Section: Discussionsupporting
confidence: 88%
“…In several brain nuclei histamine increases neuronal excitability through a dual-action mediated by H 1 and H 2 receptors (see for instance McCormick and Williamson, 1991;Ji et al, 2018;Zhuang et al, 2018). The H 1 R-mediated excitatory effect involves a mixed ionic mechanism, namely closing of K + channels, activation of Na + channels and stimulation of the Na + -Ca 2+ exchanger (McCormick and Williamson, 1991;Cilz and Lei, 2017;Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of evidence from in‐vitro studies and in vivo studies on Hdc and Hrh3 KO mice that Hrh3 regulates striatal activity . In addition, Hrh1 and Hrh2 are also present on the soma of MSN and other striatal cells and could contribute to adjusting MSN level of activity …”
Section: Discussionmentioning
confidence: 99%
“…7,10,[46][47][48] In addition, Hrh1 and Hrh2 are also present on the soma of MSN and other striatal cells and could contribute to adjusting MSN level of activity. 49 Given these data and studies that have shown regulation of striatal opioids by Hrh3, we hypothesized that striatal opioid systems might be altered in Hdc KO mice and analyzed gene expression of dynorphin and enkephalin. We found decreased dynorphin and enkephalin expression in the striatum of Hdc KO mice.…”
Section: Histamine May Indirectly Modulate Dopamine Release Throughmentioning
confidence: 99%
“…Interestingly enough, in the striatum, the main MAO isoform expressed is type B, which is the enzyme involved in T1AM (but also dopamine) degradation ( 20 ). Furthermore, other recent evidence also indicates that the release of dopamine in the striatum may be controlled by histamine released from the tuberomammillary nucleus, via H1 and H2 receptors ( 38 ). Overall, these results suggest T1AM might sustain dopamine synthesis and release acting at high-affinity targets (TAARs) and, indirectly, releasing histamine from the hypothalamic neurons.…”
Section: T1am Pharmacokineticmentioning
confidence: 99%